Enhancement of the free residual chlorine concentration at the ends of the water supply network: Case study of Souk Ahras city – Algeria - Mohamed A.; BENSOLTANE; ABD, Lotfi ZEGHADNIA; Lakhdar DJEMILI; Abdalhak GHEID; Yassine DJEBBAR (JOURNAL OF WATER AND LAND DEVELOPMENT, 2018)
The drinking-water supply sector has mostly targeted the water-borne transmission of pathogens. The most common method employed is the chlorination of drinking-water at treatment plants and in the distribution systems. In Algeria, the use of chlorine in drinking water treatment is a widespread practice. To enhance the concentration of the residual chlorine in the public water-supply system of a part of Souk Ahras city (Faubourg) (Algeria) known by its low concentration of the free residual chlorine (according to the water utility – Algérienne des Eaux: ADE investigation) especially at the point of use, practical steps were carried out. The method is a combination between numerical simulation using EPANET2 software and field measurements. Using statistical analysis the hydraulic model was calibrated and the observed values were very closer to the simulated results. The concentration was improved throughout the network after the injection of the appropriate dose.